Anxiety and Hope in Emily Bronte's Poems: A Structural Analysis - SARASWATI, TITIEN (2011)
This study aims to explore the meaning of Anxiety and Hope in Emily Bronte's poems. The objective of this research is to analyze the poem based on its structural elements. The research employs a qualitative method. In this method, the researcher used two data sources, namely primary and secondary data sources. The primary data sources are Emily Bronte's poems, namely: Anticipation, A Day Dream, A Death Scene, Death, Faith and Despondency, Honour's Martyr, Hope, How Clear She Shines, My Comforter, Remembrance, The Old Stoic, The Philosopher, Plead for Me, The Prisoner, Self Interrogation, Song, Stanzas, Stanzas To, Stars, Sympathy, and To Imagination. The secondary data sources are reference and material related to the study. The method of data collection is library research, and the technique of data collection is descriptive technique. This study comes to following conclusion. First, based on the structural elements, it was found that the speakers in Emily Bronte's poems are mostly a girl who always feels sad and always wants a clear hope to come, although there are also another speakers in those poems. Spoken to: the speakers tell to the readers what they feel, and they also speak to their beloved about their hope and anxiety. The occasion: when the speaker is reminding the beloved, in hopeless, and sad situation. Second, anxiety and hope represent the dominant themes the poems, because they are related to the writer's life.